Utilization of Used Polystyrene As Adhesive In Polymer Emulsion Asphalt - Wirjosentono, Basuki; Gustira, Rinna Ayu; Muis, Yugia (Journal of Chemical Natural Resources, 2021)
The utilization of used polystyrene as adhesive material for emulsion polymer asphalt has been carried out. Polystyrene foam was dissolved in toluene at the ratio of 30:70 mL, then the solution was mixed with aquadest at ratios of 90: 10 mL, 70: 30 mL, 50: 50 mL, 30:70 mL, and 10: 90 mL. Then added with 10 mL of Sodium Dodecyl Sulfate solution at concentrations of 10%, 20%, and 30%. The most stable latex polystyrene was mixed with 200 g of sand aggregate at volume ratios of 10 mL, 20 mL, 30 mL, 40 mL, and 50 mL. Then the mixture was pressed into a hotpress at 150ÂºC for 20 minutes. The mixture obtained was characterized using tensile strength testing, water absorption, and SEM spectroscopy. The results showed that the mixture of sand aggregate with 50 mL latex polystyrene has the best compressive strength and water absorption, at a load of 1606 Kg.f, a stroke of 14.93 mm/minutes, and a water absorption percentage of 18%. The morphology result showed that the surface of sand aggregate with 50 mL of latex polystyrene mixture contains smaller and least holes than the surface of sand aggregate with 10 mL of latex polystyrene mixture.